Posterior Restoration Selection Among General Dental Practices in Malaysia: A Preliminary Study - Abdul Azim Asy Abdul Aziz; Aimi Amalina Ahmad; Aws Hashim Ali Al-Kadhim; Azlan Jaafar; Norazlina Mohammad (Int Islamic Univ Malaysia, Kulliyyah Medicine, 2024)
Indexed by WOS